(untitled) (The Himalayan Geographers, 2025)
This paper analyzes the trend in three components of the utilization of maternal health care-antenatal care, delivery care, and postnatal care in Nepal. Notwithstanding advances in medical science and numerous efforts to improve maternal health care services, maternal health remains a major challenge in developing countries. It relies on data from the Nepal Demographic and Health Survey conducted in 2006, 2011, 2016, and 2022. Data for the present study covered 4,066 women in 2006, 4,148 in 2011, 3,998 in 2016, and 1933 in 2022 who had utilized antenatal care. The analysis confines itself to women aged 15-49 years who had a live birth in the five years preceding the survey. Data on childbirth and postnatal care were obtained from a total of 2,030 women in 2011 and 1,978 women in 2016 who had a live birth in the two years preceding the survey. The utilization of ANC by skilled health providers increased substantially from 44 per cent in 2006 to 84 per cent in 2016, respectively. However, six per cent of women do not seek even one-time ANC care, and the percentage of women who seek four or more ANC care from a skilled service provider is low. Similarly, still, there are two-fifths of deliveries that take place at home. Postnatal service utilization is still very low in Nepal. Hence, there is a need for efforts to improve the utilization of maternal healthcare services, including postnatal checkups and delivery assisted by skilled attendants.